Economic Burden of Sars-cov-2 Patients with Multi-morbidity: A Systematic Review Protocol - Amirah Azzeri; Mohd Noor Afiq Ramlee; Mohd Iqbal Mohd Noor; Mohd Hafiz Jaafar; Thinni Nurul Rochmah; Maznah Dahlui (MDPI, 2024)
Indexed by WOS/Scopus/ERA